Kapasitas Petani Padi dalam Mengakses Kredit Usaha Rakyat (KUR) di Kecamatan Pameungpeuk Kabupaten Garut, Jawa Barat - Nurholis, Muhamad Sandi; Anwarudin, Oeng; Makhmudi, Maspur (Politeknik Pembangunan Pertanian Bogor, 2020)
The Ministry of Agriculture has a strategic flagship program to improve the well-being of farmers. One of its programs is People's Business Credit (KUR). The KUR program is expected to be a solution for farmers in providing financial capital from formal financial institutions. Capitalization is a major issue facing farmers. Capital constraints also result in lower quantity and quality of yield. Thus, farmers still have low accessibility of farmers to KUR. This is because farmers consider capital access to formal financial institutions difficult and they need to have a reserve. All this time farmers have been relying on collectors and non-bankers for capital raising. Farmers need to lend capital to cultivators because they are the only easy solution to working capital. This study aimed to describe the capacity of rice farmers in accessing People's Business Credit (KUR) and to analyze the factors that influence the capacity of farmers in accessing the CURS sample of 54 people with purposive sampling technique. The research variables consisted of respondents 'characteristics, support for counseling services, social support and farmers' capacity. Data analysis techniques use descriptive statistics and multiple linear regression analysis statistics. The results can be concluded that the capacity of rice farmers in accessing KUR is in the high category. Farmers' capacity is influenced by long-term entrepreneurship, counseling service support and social support.